Agilent gene expression microarray raw data for STO-3 - Johansson, Annelie; Lindström, Linda (Karolinska Institutet, 2022)
Agilent microarray profiling of primary breast tumors in the Stockholm tamoxifen trial (STO-3) was performed in 2014. The STO-3 trial enrolled 1780 postmenopausal lymph node-negative patients with tumors smaller than or equal to 30 mm and were randomized to tamoxifen vs no endocrine therapy. Molecular analysis was possible for 808 patients with available formalin-fixed paraffin-embedded (FFPE) tissue blocks from the primary breast cancer tumor. Eighty-one patients were excluded from analysis due to insufficient invasive tumor cells, leaving 727 samples available for further analysis. Gene expression data were independently generated using custom-designed arrays, Agilent Technologies (CA, USA), containing approximately 32.1K probes, representing approximately 21.5K unique genes from FFPE breast cancer tumor tissue. 652 of 727 breast cancer tumors passed the RNA quality check according to the diagnostic quality model and were used in the analysis, of which 538 were ER-positive.

The datasetet consists of a table in one (1) txt file containing: Gene expression data (Agilent custom 32K microarray) generated in 2014 for 652 primary tumors from the STO-3 trial. The variables are the 31195 probes included in the Agilent microarray used to generate the data.
File name: STO3_Agilent_microarray_gMeanSignals_652.txt

The 31195 probes included in the Agilent microarray used to generate the data are listed and mapped to gene names in an annotation file.
Annotation file name: List_of_probes_STO3_Agilent_microarray_gMeanSignals_652.txt

Agilent microarray data genererades 2014 för primära brösttumörer i den kliniska studien STO-3 för postmenopausala lymfkörtelnegativa patienter med tumörer mindre än eller lika med 30 mm.

En utförligare beskrivning finns i den engelska versionen av katalogposten.

Datasetet består av en tabell i en (1) txt-fil innehållande: Genuttrycksdata (Agilent custom 32K microarray) genererat år 2014 för 652 primära tumörer från STO-3 studien. Variablerna är de 31195 sonder som ingår i den Alilent microarray vilken använts för att generera datasetet.
Filnamn: STO3_Agilent_microarray_gMeanSignals_652.txt

De 31195 sonder som ingår i den Alilent microarray vilken använts för att generera datasetet finns listade och mappade till gen-namn i en annotationsfil.
Filnamn annotationsfil: List_of_probes_STO3_Agilent_microarray_gMeanSignals_652.txt
Agilent genuttryck microarray rådata för STO-3
Keywords: Breast Neoplasms; Brösttumörer; Tamoxifen; Tamoxifen; Gene Expression; Genuttryck; Clinical Trial; Klinisk prövning [Publikationstyp]; Genetics and Genomics; Genetik och genomik; Cancer and Oncology; Cancer och onkologi